Manageability, availability and performance in porcupine a highly scalable, cluster-based mail service. - Saito, Yasushi (ACM transactions on computer systems.)
This paper describes the motivation, design and performance of Porcupine, a scalable mail server. The goal of Porcupine is to provide a highly available and scalable electronic mail service using a large cluster of commodity PCs. We designed Porcupine to be easy to manage by emphasizing dynamic load balancing, automatic configuration, and graceful degradation in the presence of failures. Key to the system's manageability, availability, and performance is that sessions, data, and underlying services are distributed homogeneously and dynamically across nodes in a cluster.